2018
DOI: 10.1136/jmedgenet-2018-105421
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic mutations in EXOC3L2 cause a novel syndrome that affects the brain, kidney and blood

Abstract: BackgroundDandy-Walker malformation features agenesis/hypoplasia of the cerebellar vermis, cystic dilatation of the fourth ventricle and enlargement of posterior fossa. Although Dandy-Walker malformation is relatively common and several genes were linked to the syndrome, the genetic cause in the majority of cases is unknown.ObjectiveTo identify the mutated gene responsible for Dandy-Walker malformation, kidney disease and bone marrow failure in four patients from two unrelated families.MethodsMedical assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The genes with the 10% highest weights in the current MR IVW analysis were associated with monocyte-macrophage function including migration, cytokines, and receptors, exemplified by, among others, CCR2 , EXOC3L2 , and LYZ (eTable 7 in Supplement 2). These genes have previously been reported to associate with immunodeficiency, AD, or amyloidosis, and thus further support the present findings . The present observed associations between peripheral markers of inflammation and the development of dementia may, however, not only directly be through AD pathology.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The genes with the 10% highest weights in the current MR IVW analysis were associated with monocyte-macrophage function including migration, cytokines, and receptors, exemplified by, among others, CCR2 , EXOC3L2 , and LYZ (eTable 7 in Supplement 2). These genes have previously been reported to associate with immunodeficiency, AD, or amyloidosis, and thus further support the present findings . The present observed associations between peripheral markers of inflammation and the development of dementia may, however, not only directly be through AD pathology.…”
Section: Discussionsupporting
confidence: 92%
“…These genes have previously been reported to associate with immunodeficiency, AD, or amyloidosis, and thus further support the present findings. 31,34,35 The present observed associations between peripheral markers of inflammation and the development of dementia may, however, not only directly be through AD pathology. Monocyte function may also predispose to other health conditions or comorbidities that ultimately influence cognition outside the AD pathogenesis.…”
Section: Discussionmentioning
confidence: 72%
“…A genetic anomaly of Sec15 and downregulation are involved in neurodevelopmental abnormalities related to language abilities [40][41][42]. SEC5 and SEC6 variants also affect brain development, presenting severe hypoplastic hippocampi and shrinking cerebellum [43,44]. Outside those reports, only one has studied Exocyst's involvement in neurodegenerative diseases such as Alzheimer's, where Sec6 has been associated with brain glucose metabolism abnormalities [45].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, novel mutations of EXOC3L2 were found in two families with Dandy–Walker malformation (DWM) (Shalata et al 2019 ) (Table 1 ), which primarily affects cerebellar development and is often associated with ciliopathies. One family was consanguineous and had three aborted fetuses, all diagnosed with DWM, carrying the homozygous c.122T > A; p.Leu41Gln mutation in EXOC3L2 .…”
Section: Introductionmentioning
confidence: 99%